Implementasi Prinsip Net Zero Energy Building (NZEB) pada Bangunan Tinggi di Iklim Tropis: Studi Kasus TechnoPark Tower, Hanoi - Lestari, Suci; Dewi, Ayu Komalasari; Putri , Tiya Suryadi; Faris, Moh. Faisal (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2026)
The need to reduce the impact of climate change has pushed the development of buildings that use less energy, including the idea of Net Zero Energy Building (NZEB). NZEB means a building can produce as much energy as it uses in a year, usually from renewable sources. This study looks at how NZEB is applied in TechnoPark Tower, Hanoi, as an example of a tall building in a tropical climate. The method used is descriptiveanalytical, based on literature review, observation of design strategies, and evaluation of the building’s energy performance.The results show that the biggest challenge in tropical high-rise buildings is the high need for cooling, because of strong sunlight and high humidity. To deal with this, the building uses passive design strategies such as proper orientation, double-layer façades, and shading elements to reduce heat from the sun. These are supported by active systems like efficient air conditioning, smart energy control, and the use of renewable energy such as solar panels. Because the roof area is limited, additional solar systems are also used outside the main building area. In conclusion, applying NZEB in high-rise buildings needs a good mix between design and technology. TechnoPark Tower shows that even in tropical conditions, energy efficiency can still be achieved, and it can be a useful example for future building design.